1998
DOI: 10.1128/mcb.18.5.2932
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Deficiency Reduces the Abundance of mRNA for Se-Dependent Glutathione Peroxidase 1 by a UGA-Dependent Mechanism Likely To Be Nonsense Codon-Mediated Decay of Cytoplasmic mRNA

Abstract: The mammalian mRNA for selenium-dependent glutathione peroxidase 1 (Se-GPx1) contains a UGA codon that is recognized as a codon for the nonstandard amino acid selenocysteine (Sec). Inadequate concentrations of selenium (Se) result in a decrease in Se-GPx1 mRNA abundance by an uncharacterized mechanism that may be dependent on translation, independent of translation, or both. In this study, we have begun to elucidate this mechanism. We demonstrate using hepatocytes from rats fed either a Se-supplemented or Se-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(198 citation statements)
references
References 49 publications
8
188
1
1
Order By: Relevance
“…Figure 4C shows that GPX2 levels were not detectable in PC-3 or LNCaP cells, even in the presence of added selenium. In addition, and consistent with GPX1, selenium supple- npg This is consistent with the protein levels observed in Figure 4A and the previous reports showing that GPX1 mRNA is unstable when selenium is deficient [21][22][23][24]. GPX4 mRNA levels are not as consistent with protein levels since clear expression is detectable even in PC-3 cells under low selenium conditions where GPX4 protein is lacking, indicating a clear case of regulation at the translational level.…”
Section: Gpx2 Expression Is Only Detected In Rwpe-1 Prostate Cellssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 4C shows that GPX2 levels were not detectable in PC-3 or LNCaP cells, even in the presence of added selenium. In addition, and consistent with GPX1, selenium supple- npg This is consistent with the protein levels observed in Figure 4A and the previous reports showing that GPX1 mRNA is unstable when selenium is deficient [21][22][23][24]. GPX4 mRNA levels are not as consistent with protein levels since clear expression is detectable even in PC-3 cells under low selenium conditions where GPX4 protein is lacking, indicating a clear case of regulation at the translational level.…”
Section: Gpx2 Expression Is Only Detected In Rwpe-1 Prostate Cellssupporting
confidence: 91%
“…This is also true for GPX1, but to a lesser extent, because mRNA levels in the absence of selenium supplementation are reduced. This is very likely to be the result of lower mRNA stability as has been observed for GPX1 in multiple studies [21][22][23][24]. In the case of GPX2, the expression observed appears to be dramatically regulated at the RNA level, most likely at the level of transcription because its mRNA is not detectable even in the presence of supplemental selenium.…”
Section: Discussionmentioning
confidence: 89%
“…Putative NMD-inducing features included upstream open reading frames (uORFs; 70 transcripts), alternative splicing that introduces nonsense codons or frameshifts (21 transcripts, some of which undergo alternative splicing specifically in HeLa cells 12,13 ) and introns in the 3¢ untranslated region (UTR; 9 transcripts). Two transcripts encoding proteins containing selenocysteine were also upregulated, consistent with the alternative recognition of the UGA selenocysteine codon as a signal for translation termination 14 . Additionally, we observed upregulation of nonfunctional transcripts derived from mariner 2 transposon (HSMAR2) remnants and human endogenous retrovirus H (HERV-H) sequences that have acquired premature termination codons (PTCs) during evolution.…”
Section: E T T E R Smentioning
confidence: 70%
“…The idea that an intronless gene generates mRNA that is subject to NMD has also been negated by our studies demonstrating that expression of an intronless gene for glutathione peroxidase (GPx) 1 under conditions of selenium deficiency fails to increase the efficiency of NMD despite increasing the efficiency with which the Sec (TGA) codon is recognized as nonsense (Moriarty et al+, 1997)+ Furthermore, converting the Sec codon to a TAA nonsense codon in the context of an intronless GPx1 allele does not change the level of GPx1 mRNA, despite the fact that the TAA codon is recognized as nonsense more efficiently than the Sec codon, regardless of the Se concentration (Moriarty et al+, 1997)+ In contrast, expression of the full-length GPx1 gene under conditions of Se deficiency or expression of the full-length GPx1 gene harboring a TAA nonsense codon in place of the Sec codon does increase the efficiency of NMD, as would be expected considering that the sole intron is situated 105 bp (i+e+, more than 50-55 bp) downstream of the Sec codon (Moriarty et al+, 1997(Moriarty et al+, , 1998)+…”
Section: Evidence That the 39-most Exon-exon Junction Is Not A Positimentioning
confidence: 99%
“…In mammals, as in all organisms examined, mRNAs that prematurely terminate translation are abnormally reduced in abundance by a mechanism called nonsense-mediated mRNA decay (NMD) or mRNA surveillance (for reviews, see Maquat, 1995Maquat, , 1996Li & Wilkinson, 1998;Culbertson, 1999;Hentze & Kulozik, 1999;Hilleren & Parker, 1999)+ This mechanism is thought to have evolved to eliminate nonsense-containing RNAs that arise as a consequence of (1) mutations in germ-line or somatic DNA or (2) routine abnormalities in gene expression due to abnormalities in, for example, transcription initiation, splicing, and somatic rearrangements of the type that characterize the immunoglobulin and T-cell receptor genes+ The elimination of nonsense-containing mRNAs protects cells from the potentially deleterious effects of the encoded truncated proteins, which can manifest new or dominant-negative functions (Kazazian et al+, 1992;Pulak & Anderson, 1993;Hall & Thein, 1994;Cali & Anderson, 1998)+ In addition to eliminating abnormal transcripts, NMD also regulates the expression of certain mRNAs that are not abnormal+ Examples in mammalian cells are provided by certain selenoprotein mRNAs that terminate translation at a UGA codon for the inefficiently incorporated amino acid selenocysteine (Sec; Moriarty et al+, 1997Moriarty et al+, , 1998+ Other examples will undoubtedly resemble natural substrates found in other organisms such as the alternatively spliced mRNAs of Caenorhabditis elegans that retain an internal exon harboring an in-frame termination codon (Morrison et al+, 1997), and transcripts of Saccharomyces cerevisiae that contain a small open reading frame upstream of the primary open reading frame (Leeds et al+, 1992;Pierrat et al+, 1993)+ Based on studies of disease-associated and in vitromutagenized genes, a rule for termination-codon position within intron-containing genes has been established for mammalian cells: only those termination codons located more than 50-55 nt upstream of the 39-most exon-exon junction mediate mRNA decay (Cheng et al+, 1994;Thermann et al+, 1998;Zhang et al+, 1998aZhang et al+, , 1998b)+ In support of this rule, more than 98% of genes having one or more 39-untranslated exons terminate translation less than 50 nt upstream of the 39-most exon-exon junction (Nagy & Maquat, 1998)+ There is a growing consensus that exon-exon junctions function in NMD+ According to current thinking, the process of pre-mRNA splicing influences product mRNP structure and, in so doing, NMD, by leaving a mark at the junctions ...…”
Section: Introductionmentioning
confidence: 99%